(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The article analyzes epoxy resins, which are products of condensation of polyatomic phenols (diphenylolpropane, resorcinol) with compounds containing an epoxy group, such as glycerin epichlorohydrin, glycerin diglycidal ester, glycerin dichlorohydrin. Epoxy resins are products of the reaction of diphenylolpropane with epichlorohydrin. They are used both in pure form and as a starting material for the production of epoxy compounds.